Periostin expression in uninvolved skin as a potential biomarker for rapid cutaneous progression in systemic sclerosis patients: a preliminary explorative study - De Luca, Giacomo; Campochiaro, Corrado; Burastero, Samuele E.; Matucci-Cerinic, Marco; Doglioni, Claudio; Dagna, Lorenzo (Frontiers in Medicine, 2024)
Objectives This study aimed to evaluate periostin serum levels and skin expression in patients with systemic sclerosis (SSc). Methods We enrolled 35 patients with diffuse (d-SSc) or limited (l-SSc) SSc, 15 patients with very early diagnosis of systemic sclerosis (VEDOSS), and 30 sex-matched healthy controls. Periostin serum levels were determined by an enzyme-linked immunosorbent assay (ELISA). Periostin skin expression was determined by immunohistochemistry (IHC) on paired involved and uninvolved 5-mm skin biopsy samples in a subgroup of 10 d-SSc and 10 L-SSc patients. A 12-month follow-up was considered. Results We included 50 patients (mean age 53.1 ± 16.1 years; women 94%; mean disease duration 38.2 ± 45.1 months; anti-centromere 50%; anti-Scl70 40%), 35 of them with a definite SSc (68.8% l-SSc; 31.4% d-SSc; mean mRSS 9.0 ± 7.2) and 15 with VEDOSS; 30 controls were also included in this study. Periostin serum levels were higher in SSc patients compared to controls (32.7 ± 8.0 ng/mL vs. 27.7 ± 7.3 ng/mL; p < 0.001), while these levels were comparable among different groups of patients (29.7 ± 6.9 ng/mL in VEDOSS, 33.4 ± 7.8 ng/mL in lc-SSc; and 34.0 ± 8.5 in dc-SSc; p = ns). SSc patients with digital ulcers had higher periostin serum levels (36.2 ± 7.9 ng/mL vs. 30.6 ± 7.3 ng/mL, p < 0.02). Samples from the involved skin of l-SSc and d-SSc patients showed a significant dermal expression of periostin; an identical periostin expression was evident in the uninvolved skin of patients with d-SSc. In 7 out of 10 L-SSc patients, periostin expression was absent on uninvolved skin. In the remaining three l-SSc patients, a mild periostin expression on IHC was detectable on uninvolved skin and all of these three l-SSc patients presented a dramatic skin progression. Conclusion Periostin skin expression may be a useful biomarker to indicate the presence of a disease at a higher risk of rapid cutaneous involvement.